Downregulation of the histone methyltransferase SETD2 promotes imatinib resistance in chronic myeloid leukaemia cells - Sheng, Yaru (Cell Prolif, 2019)
OBJECTIVES: Epigenetic modifiers were important players in the development of haematological malignancies and sensitivity to therapy. Mutations of SET domain‐containing 2 (SETD2), a methyltransferase that catalyses the trimethylation of histone 3 on lysine 36 (H3K36me3), were found in various myeloid malignancies. However, the detailed mechanisms through which SETD2 confers chronic myeloid leukaemia progression and resistance to therapy targeting on BCR‐ABL remain unclear. MATERIALS AND METHODS: The level of SETD2 in imatinib‐sensitive and imatinib‐resistant chronic myeloid leukaemia (CML) cells was examined by immunoblotting and quantitative real‐time PCR. We analysed CD34(+)CD38(−) leukaemic stem cells by flow cytometry and colony formation assays upon SETD2 knockdown or overexpression. The impact of SETD2 expression alterations or small‐molecule inhibitor JIB‐04 targeting H3K36me3 loss on imatinib sensitivity was assessed by IC50, cell apoptosis and proliferation assays. Finally, RNA sequencing and ChIP‐quantitative PCR were performed to verify putative downstream targets. RESULTS: SETD2 was found to act as a tumour suppressor in CML. The novel oncogenic targets MYCN and ERG were shown to be the direct downstream targets of SETD2, where their overexpression induced by SETD2 knockdown caused imatinib insensitivity and leukaemic stem cell enrichment in CML cell lines. Treatment with JIB‐04, an inhibitor that restores H3K36me3 levels through blockade of its demethylation, successfully improved the cell imatinib sensitivity and enhanced the chemotherapeutic effect. CONCLUSIONS: Our study not only emphasizes the regulatory mechanism of SETD2 in CML, but also provides promising therapeutic strategies for overcoming the imatinib resistance in patients with CML.